Self Efficacy, Trust Toward Leader dan Pengaruhnya terhadap Perilaku Kerja Inovatif - Ch. Ndaru Tyas S. (EXERO : Journal of Research in Business and Economics, 2021)
This study aims to examine whether self efficacy has positive influence on innovative work behavior of teachers (innovative work behavior) and whether trust in leadership (trust toward leader) positive effect on the innovative behavior of teachers (innovative work behavior). This study uses the theory of Phillip and Gully (1997) to consider the positive influence between self efficacy and innovative behavior of teachers (innovative work behavior), as well as the theory of Mayer and Davis (1995) to consider the positive effect of trust in leadership (trust toward the leader) on behavior innovative teachers (innovative work behavior. To measure self efficacy, this study used an instrument developed by Bandura (1997). To measure trust toward the leader, this study used an instrument developed by Meyer and Allen (1991). Instrument testing was done by using the validity testing corrected item-total correlation, and reliability testing Cronbachs Alpa. These results support the hypothesis that self efficacy has positive influence on innovative behavior of teachers (innovative work behavior), as well as confidence in the leadership hypothesis (trust toward leader) positive effect on teachers' innovative work behavior (innovative work behavior).